Odpowiedzi

Najlepsza Odpowiedź!
2010-02-11T19:10:45+01:00
A) (a+b)-(2a-b)-(a-2b) = a+b-2a+b-a+2b = -2a +4b
b) (3x-y+1)-(x+y)+(y-x) = 3x-y+1-x-y+y-x = x-y+1
c) -(kx+ny)-(3kx+2ny)+(5kx-3ny) = -kx-ny-3kx-2ny+5kx-3ny =
kx -6ny
d) (2ab+a+3)-(3ab-a+3)= 2ab+a+3 -3ab+a-3 = -ab+2a
e) (4x²-3x)-(x+0,1x²)-(x²-0,1x) = 4x²-3x-x-0,1x²-x²+0,1x =
2,9x²-3,9x
1 5 1
2010-02-11T19:13:12+01:00
A) a+b-2a-b-a+2b=-2a+2b
b) 3x-y+1-x-y+x-y=3x-3y
c) -kx+ny-3kx-2ny+5kx-3ny= kx-4ny
d)2ab+a+3-3ab+a-3=ab+2a-3
e)4^2-3x-x-0,1x^2-x^2+0,1x= -------------------------
2010-02-11T19:57:10+01:00
A) a+b-2a+b-a+2b= -2a+4b
b) 3x-y+1-x-y+y-x= 4x+3y+1 lub 1x-y+1
c)-kx-ny-3x-2ny+5kx-3ny=1kxlub9kx
d)2ab+a+3-3ab+a-3=2a-1b
e)4x^2-3x-x-0,1x^2-x^2+0,1x=3,1x^2+3,1